Community Participation in the Development Planning Process of the Village Area - Ahmad Ahmad; Barkah Rosadi; Susniwati Susniwati (Innovation Business Management and Accounting Journal, 2024)
The implementation of mandatory actions required by Law No. 23 of 2014 concerning Regional Government, Article 150, mandates that development planning is a mandatory affair. Development planning as carried out in Sekeloa Sub-District is through a participatory planning process known as "musrenbang", which begins with a sub-district-level deliberation and continues at the district-level musrenbang. This research aims to define and analyze the process of sub-district development planning, community involvement, as well as the variables that drive and hinder it. The research methodology employs an interactive qualitative data analysis model for descriptive research with a qualitative approach. The findings of this research indicate active community involvement in the musrenbang of Sekeloa Sub-District. In this phenomenon, the community and the government collaborate in Sekeloa Sub-District to plan for future growth. The active participation of both the community and the government in the development planning process of Sekeloa Sub-District highlights a collaborative effort towards sustainable growth and development. This partnership underscores the importance of inclusive decision-making and community empowerment in shaping the future of the locality.